Implementation And Performance Analysis Development Security Operations (DevSecOps) using Static Analysis and Security Testing (SAST) - Wedy Freddy Santoso; Dadang Syarif Sihabudin Sahid (International ABEC, 2021)
DevSecOps solves the problem by integrating the security of development operations through various development life cycles. benefits, implementation and challenges during the process. in addition to many documented web hacks. For the scope of work reported that the focus is on two widely used digital library systems: DSpace and Greenstone, in performing Static Application Security Testing (SAST) in addition to more traditional port scanning. Weaknesses were found and details how to make improvements to both systems to make them more secure. can ensure by considering more broadly on the forms of security problems found, to assist the development of software architecture in the future.